2002
DOI: 10.2746/042516402776185985
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic approach to assess irrelevant plasma or urine drug concentrations in postcompetition samples for drug control in the horse

Abstract: The current performance of analytical techniques used for drug control in horses lead the Regulatory Authorities to decide whether trace levels of drugs legitimately used for therapeutic medication should or should not be reported. Here, we propose a well-ordered and nonexperimental pharmacokinetic/pharmacodynamic approach for the determination of irrelevant drug plasma (IPC) and urine concentrations (IUC). The published plasma clearance is used to transform an effective (marketed) dose into an effective conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 9 publications
2
102
0
Order By: Relevance
“…There are two factors of variability to be considered when deciding a withdrawal time 1) the biological variability between horses for drug disposition, that is the pharmacokinetic (PK) parameters controlling plasma and urine drug disposition [2,3]; this first source of variability is explained by factors (hereafter termed covariates) such as breed, age, sex, health status 2) the different sources of uncertainty associated with veterinary and/or trainer practice such as the actual administered dose, protocol of administration, trained/untrained conditions. All these sources of variability generate a large population of individual detection times, and the proportion (percentiles) of horses attaining a given detection time value for a given screening limit cannot be determined due to the limited number of horses enrolled in an EHSLC trial [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are two factors of variability to be considered when deciding a withdrawal time 1) the biological variability between horses for drug disposition, that is the pharmacokinetic (PK) parameters controlling plasma and urine drug disposition [2,3]; this first source of variability is explained by factors (hereafter termed covariates) such as breed, age, sex, health status 2) the different sources of uncertainty associated with veterinary and/or trainer practice such as the actual administered dose, protocol of administration, trained/untrained conditions. All these sources of variability generate a large population of individual detection times, and the proportion (percentiles) of horses attaining a given detection time value for a given screening limit cannot be determined due to the limited number of horses enrolled in an EHSLC trial [2].…”
Section: Introductionmentioning
confidence: 99%
“…The main metabolite previously reported in horse plasma was hydroxyethylpromazine [2]. Pilot studies conducted before the start of this present work (data not shown) suggested that acepromazine and hydroxyethylpromazine would be the most suitable analytes in plasma for detecting the use of acepromazine.…”
Section: Analysis Of Acepromazine and Metabolites In Horse Plasmamentioning
confidence: 71%
“…It is also used in veterinary medicine as a pre-anaesthetic agent for surgical procedures, enabling a lower dose of anaesthetic to be used and, hence, quicker and smoother recovery [1]. The presence of pharmacologically significant concentrations of acepromazine in racehorses on race days is prohibited by the British Horseracing Authority (BHA) and many other horseracing and equestrian sport authorities [2]. In this study, the detection of acepromazine and its metabolites in post-administration samples was further investigated to better advise on the withdrawal of this medication ahead of competition.…”
Section: Introductionmentioning
confidence: 99%
“…These threshold levels were based on several studies [5, 7, 8], in which the average urine concentration of SA was dependent on the horse’s diet and country of origin. However, the thresholds were established on a arbitrary statistical basis and not extrapolated from any irrelevant plasma or urine concentration as proposed by Toutain and Lassourd [9]. …”
Section: Introductionmentioning
confidence: 99%